Parameter selection of autocorrelation test for block ciphers - FAN Li-min1; FENG Deng-guo1; ZHOU Yong-bin1 (Tongxin xuebao)
Autocorrelation test was a statistical test to evaluate the correlation between one sequence and the corresponding non-cyclic left-shifted d bits sequence.It was impractical to adopt all the values of d since its range was often very wide.Three relations between parameters of randomness test were defined firstly.Then the relationships among the subclass D={1,2,m/4,m/2,3m/4,m,2m}of autocorrelation test for block cipher were studied by statistical experiments,where m was block length.The experiments show that the prefer choice of parameter d is m when doing autocorrelation test for block cipher.The method is also available for parameter selection of other randomness test for other types of cryptosystem.